2023
DOI: 10.3390/genes14101904
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism Analysis of 24 Y-STRs in a Han Chinese Population in Luzhou, Southwest China

Jiewen Fu,
Binghui Song,
Jie Qian
et al.

Abstract: Han is the largest of China’s 56 ethnic groups and the most populous ethnic group in the world. The Luzhou region is located in southwest China, at the junction of three provinces. The unique historical factors contribute to the genetic polymorphism information. Short tandem repeats (STRs) are highly polymorphic, but the polymorphism of the Y chromosomal STRs (Y-STRs) loci in the Luzhou region is still unclear. It is of great significance to provide Y-STRs genetic data for the Han population from the Luzhou ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…More specifically, in the field of population genetics, Fu et al (2023) [1] investigated the genetic diversity within the Han population of Luzhou by analyzing 24 Y-chromosome Short Tandem Repeat (Y-STR) markers. Engaging 910 participants, the study identified 893 distinct haplotypes, most of which are unique, thereby underscoring significant genetic polymorphism and a high capacity for discrimination.…”
mentioning
confidence: 99%
“…More specifically, in the field of population genetics, Fu et al (2023) [1] investigated the genetic diversity within the Han population of Luzhou by analyzing 24 Y-chromosome Short Tandem Repeat (Y-STR) markers. Engaging 910 participants, the study identified 893 distinct haplotypes, most of which are unique, thereby underscoring significant genetic polymorphism and a high capacity for discrimination.…”
mentioning
confidence: 99%